Balanced cytokine upregulation by diluted ethanolic extract of Bryonia alba in Delta SARS-CoV-2 Spike protein RBD-induced pathogenesis in Gallus gallus embryo - Goswami, Pritam (2023)
Delta SARS-CoV-2 spike protein RBD antigen, in concentration of 10 µg/mL, increases IFN-α, more than 1500 times. It also increases IFN-ß about 150 times, and TGF-ß about 74 times. Increase in IFN-ƴ, IL-6, IL-8, IL-10, and IL-1ß was insignificant.When after administration of Bryonia 6C, the chick embryo was challenged with antigen, only interferons are moderately upregulated along with IL-6. Although increase in interferons after 48 h is beneficial to the embryo, an increase in IL-6 may lead to initiation of upsurge of pro-inflammatory cytokines. This may be detrimental to the normal physiological activities of the embryo, and thus, the preventive role of Bryonia 6C is questionable. In the curative experiment after administration of antigen, and then challenging with Bryonia 6C, the upregulation of IL-6 was decreased about 4 times than in the preventive study. Along with that, there was marked increase in IFN-α (5 times more as compared to the preventive group), and there was minor increase in IFN-ß. Thus, the curative role of Bryonia 6C in immune-pathological changes induced by Delta SARS-Cov-2 spike RBD was significantly more. Thus, it is expected that the side effects would be much less.